Hubungan Antara Tingkat Kesepian Dengan Parasocial Relationship Pada Remaja Penggemar K-POP di Komunitas Exo-L Lampung: The Relationship Between The Level Of Loneliness And The Parasocial Relationship Of Adolescent K-POP Fans In The Exo-L Lampung Community - Noffiyanti; Mohd Manawi Mohd Akib; Andini Fitriyani (UIN Kiai Haji Achmad Siddiq Jember, 2023)
The Mental Health Foundation states that loneliness in young people or adolescents is higher than in adults or the elderly. Someone who experiences loneliness will look for other ways to conduct a relationship using a different way. Therefore, parasocial relationships can be used to get rid of the loneliness they feel. By having a parasocial relationship with their idol, they can feel the reciprocity they don't get in the real world. This study aims to determine whether or not there is a relationship between the level of loneliness and parasocial relationship among adolescent K-Pop fans in the EXO-L Community in Lampung. This research is a quantitative-correlation study. The research sample was taken using a total sampling technique as many as 48 late teens with an age range of 18-21 years. The method of data collection in this study used a questionnaire or questionnaire. The data analysis used is the Product Moment correlation analysis from Karl Pearson assisted by the SPSS version 21 application program. The results of the study using Product Moment analysis showed a Sig. value of 0.143 > 0.05 and a correlation coefficient value of -0.215 where the value was smaller than the r-table value at a Sig. level of 5% N = 48, which was 0.291 (-0.215 < 0.291). Thus, there is no significant relationship between the level of loneliness and parasocial relationship among adolescent K-Pop fans in the EXO-L Lampung community. From the results, the alternative hypothesis (Ha) is rejected and the null hypothesis (H0) proposed by the researcher which reads